2017
DOI: 10.1111/jocn.13642
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac patients’ perceptions of their responsibilities in adherence to care: a qualitative interview study

Abstract: Autonomy is an inherent part of cardiac patients' adherence to care, but there has been little focus on their responsibilities in the literature. More attention needs to be paid to the healthcare providers' abilities to support patients' duties and responsibilities in clinical practice and to future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…When patients acknowledge the role that lifestyle behaviors play in the course of their disease, it is feasible to say that they can understand their personal control over these behaviors and their active and responsible role in disease control, including drug management, symptom recognition, and risk factor modification. 35,36 In this scenario, it is also necessary to highlight the importance of healthcare providers and educators to support and guide patients to translate that knowledge and awareness into action, which was also identified by a previous study. 37 Therefore, providing suf- ficient information is one of the steps for autonomy and accountability in adherence to care, with the role of health professionals as facilitators in the process of effective self-care engagement being crucial so that patients feel confident to self-manage their conditions.…”
Section: Discussionmentioning
confidence: 92%
“…When patients acknowledge the role that lifestyle behaviors play in the course of their disease, it is feasible to say that they can understand their personal control over these behaviors and their active and responsible role in disease control, including drug management, symptom recognition, and risk factor modification. 35,36 In this scenario, it is also necessary to highlight the importance of healthcare providers and educators to support and guide patients to translate that knowledge and awareness into action, which was also identified by a previous study. 37 Therefore, providing suf- ficient information is one of the steps for autonomy and accountability in adherence to care, with the role of health professionals as facilitators in the process of effective self-care engagement being crucial so that patients feel confident to self-manage their conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Findings on other heart patients after an acute myocardial infarction show that a sense of coherence plays a significant role in how people manage their illness and treatment (Norekval et al, ). Among other cardiac patients, the individual resources and motivation were the main factor that influenced the patients’ responsibilities concerning adherence to care (Kangasniemi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this syndrome remains a challenge to face to improve both the patients' quality of life and insulin therapy management. Literature has widely demonstrated that adherence to care is essential to patients in order to ameliorate the path of treatment of the illness [14] and that a scarce adherence to care in DM can lead to poor management of illness. Poor perception of self-efficacy in curing one's disease leads to psychological problems such as anxiety [15], depression [16], and distress [17].…”
Section: Introductionmentioning
confidence: 99%